Analysis about the Effects of Ease of Use Site, Information Quality, Purchasing Trust, and Price Impression Towards Using of Online Shopping Blibli on Community in Semarang - Endigalani, Annisa; Saraswati, Amelia; Kautsar, Fauzan; Nurdianasari, Rista (Institut Teknologi Sepuluh Nopember, 2020)
This research aims to analyze the influence of ease of use site, quality information, purchasing trust, and the impression of price against visitor’s shopping intention on Blibi. The sampling method used on this research is probability sampling with random sampling technique. Samples were collected from 258 respondents who are community in Semarang who have visited the site Blibi. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression test, t-test, f-test, determination test. The result showed that the ease of use of the site, quality informartion, purchasing trust, and the impression of price has positive influence towards the shopping intention.